Statement at the High-Level Roundtable on Humanitarian Financing - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim , World Bank Group President, spoke about how United Nations and the World Bank Group have made significant progress in working together to help the poor and the vulnerable. He discussed increasing the impact of humanitarian action in the face of new threats, such as climate change, pandemics and an unprecedented refugee crisis. He suggested three ways in which the World Bank Group and all the multilateral development banks can work together, especially in protracted humanitarian responses: First, produce new data and evidence to promote a risk-based approach, prevent crises and respond to the needs of refugees and host countries; Second, embrace the power of leveraging public funds for greater impact; Third, explore tying this funding to specific outcomes in addressing protracted humanitarian crises.